Nilai Moral dalam Cerpen Kompas Edisi November 2025 Sebagai Alternatif Bahan Ajar Bahasa Indonesia di Fase F SMA - Mahirotunnisa; Agus Setyonegoro; Rahmawati; Lusia Oktri Wini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify moral values ​​in short stories from the November 2025 edition of Kompas and assess their suitability as alternative Indonesian language teaching materials for Phase F of high school. This study used a descriptive qualitative approach with a documentation study as the data collection technique. The data sources were five short stories analyzed using Nurgiyantoro's theory of moral values. The results indicate that the moral values ​​identified encompass human relationships with oneself, fellow human beings, and God. Dominant values ​​include honesty, responsibility, empathy, solidarity, and spiritual awareness. Furthermore, the results also indicate that not all short stories from the November 2025 edition of Kompas are suitable as primary teaching materials. Differences in themes, language styles, and symbolism make some short stories difficult for students to understand without teacher guidance.